2018
DOI: 10.3855/jidc.10723
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on public belief, knowledge and practice towards antibiotic use in the state of Perak, Malaysia

Abstract: Introduction: Inappropriate use of antibiotics has led to antimicrobial resistance, a major public health challenge worldwide. This study aimed to explore beliefs, knowledge, and practice on antibiotic use among general public. Methodology: Cross-sectional study was conducted at 13 hospitals and 44 primary health clinics in Perak from May to July 2017. Adults above 18 years, literate, and had experience in antibiotics consumption were selected through sequential sampling method. Data was collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
(19 reference statements)
4
19
1
1
Order By: Relevance
“…In their study, McNulty et al also concluded that there was no simple relationship between knowledge, attitude and practice on the prudent use of antibiotics [25]. However, in this study, respondents with better knowledge regarding the need to adhere to antibiotic regimen were more likely to have completed their antibiotic course, which is in line with another Malaysian study [41]. In addition, significant associations were obtained between respondents' knowledge on antibiotic effect and their expectations of antibiotic treatment for the common cold or cough.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In their study, McNulty et al also concluded that there was no simple relationship between knowledge, attitude and practice on the prudent use of antibiotics [25]. However, in this study, respondents with better knowledge regarding the need to adhere to antibiotic regimen were more likely to have completed their antibiotic course, which is in line with another Malaysian study [41]. In addition, significant associations were obtained between respondents' knowledge on antibiotic effect and their expectations of antibiotic treatment for the common cold or cough.…”
Section: Discussionsupporting
confidence: 82%
“…In terms of knowledge regarding antibiotic use, respondents in this study were found to be confused with the role and identification of antibiotics, a finding that is in line with other Malaysian studies [28,35,37,[39][40][41]56]. Although 70.4% of respondents in this study answered correctly that antibiotics are medicines that can kill bacteria, only a small proportion of respondents (18.9%) were able to correctly identify antibiotics as being ineffective against viral infections.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This could lead to the rise of antibiotic misprescribing and/or overprescribing, further impacting the development of resistance. Thus, it is important to address one’s knowledge and beliefs of the proper antibiotic usage, hence stopping the misconceptions and expectations of using antibiotics to treat minor illnesses [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%